Comprehensive economic evaluation of enhanced recovery after surgery in hepatectomy - Yihan Dong (BMC, 2021)
Abstract Background Enhanced recovery after surgery (ERAS) is attracting extensive attention and being widely applied to reduce postoperative stress and accelerate recovery. However, the economic benefits of ERAS are less clarified at the social level. We aimed to assess the economic impact of ERAS in hepatectomy from the perspectives of patients, hospitals and society, as well as identify the approach to create the economic benefits of ERAS. Methods By combining the literature and national statistical data, the cost-effectiveness framework was clarified, and parameter values were determined. Cost-effectiveness analysis, cost–benefit analysis and cost-minimisation analysis were used to compare ERAS and conventional treatment from the perspectives of patients, hospitals and society. The capital flow diagram was used to analyse the change between them. Results ERAS significantly reduced the economic burden of disease on patients ($8935.02 vs $10,470.02). The hospital received an incremental benefit in ERAS (the incremental benefit cost ratio value is 1.09), and the total social cost was reduced ($5958.67 vs $6725.80). Capital flow diagram analysis demonstrated that the average daily cost per capita in the ERAS group increased ($669.51 vs $589.98), whereas the benefits depended on the reduction of hospital stay and productivity loss. Conclusion The mechanism by which ERAS works is to reduce the average length of stay, thereby reducing the economic burden and productivity loss on patients and promoting the hospital bed turnover rate. Therefore, ERAS should further focus on accelerating the rehabilitation process, and more economic support (such as subsidies) should be given to hospitals to carry out ERAS.